War damage as a factor determining the urban landscape on the example of the towns of north-eastern Poland and what is the result of it - Salm, Jan (City and War, 2021)
Wars have always had a significant impact on shaping the face of cities. It manifested itself through the evolution of fortifications, but also changes in urban and suburban buildings. The history of urban centers was obviously influenced by war damage, which led to a crisis, sometimes to the disappearance of an urban center. Sometimes, however, they were an impulse for slow or quick, planned or chaotic reconstruction depending on many factors. Removing the damage consisted in striving to restore the state from before the war, but usually it was also a pretext for planning reforms and corrections, which led to the deconstruction and blurring of the original system. Sometimes the reconstruction was not undertaken or limited only to selected buildings or fragments, and the suburbs took over the functions of the center. The specificity of these phenomena had (and still has!) A positive or negative impact not only on the perception of these centers, but also on their further development. The above-mentioned phenomena are well illustrated by cities located in North-Eastern Poland (Warmia-Masuria Province), i.e. in the former East Prussia. The cities of this historic land were mostly affected in the 20th century by one, and in part by double war damage, and then by very heterogeneous forms of reconstruction. Parts of the cities were either not rebuilt at all or their historic centers were replaced with blocks of flats. In the former city centers, as a result of such actions, incoherent and disarmed complexes of buildings arose. The aim of the paper is to characterize these phenomena and try to compare them. It also raises the question of whether the traditional spatial arrangement of the historic city is needed by its contemporary inhabitants. There are three cities used as examples: Pasłęk, Pieniężno and Kisielice.